The Effect of Ultrasound and Neuromuscular Taping Interventions on Reducing Pain in Non-Specific Low Back Pain Patients - Nova Relida Samosir; Siti Muawanah (Jurnal teknologi Kesehatan Borneo, 2023)
Low back pain (LBP) is a musculoskeletal disorder caused by poor ergonomics. LBP is defined as pain localized between the costal margin and the inferior gluteal fold that lasts for more than one day. The purpose of this study was to determine the effect of Ultrasound and Neuromuscular Taping interventions on reducing non-specific low back pain. This study used a quasi-experimental method with a one-group pre-and post-test design, and the research sample was given Ultrasound and Neuromuscular Taping interventions. The pain measurement tool used was the Visual Analog Scale (VAS). The normality test was performed using the Shapiro-Wilk test, and the effect test was performed using the Wilcoxon test. The results of this study showed that the pre-and post-intervention mean VAS scores were 6.7±1.766 and 1.7±0.674, respectively. With a value of p = 0.005 (p < 0.005), which indicates a significant difference between the VAS scores before and after Ultrasound and Neuromuscular Taping interventions. This value can be interpreted as evidence that the combination of these two interventions can reduce the degree of pain in non-specific low back pain conditions. In conclusion, the study found that there was a significant effect of Ultrasound and neuro-muscular taping (NMT) interventions on reducing pain in cases of non-specific low back pain.